A negative electrode sheet, a preparation method thereof, a solid-state battery, and an electric device
Patent Information
- Application Number
- CN202510496235.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2026-10-23
AI Technical Summary
[0002]为了提升固态电池的能量密度,负极往往采用高容量型的纯硅负极材料,然而纯硅负极电极整体压实密度较低,孔隙率较高,在固态电池中,极片中没有电解液,孔隙结构的存在严重影响了离子和电子传输
[0020]通过上述技术方案,本公开通过在负极极片中添加滑石粉,滑石粉的复合层状结构具有良好的润滑性,可以改善含硅颗粒在与集流体复合过程中的颗粒重排,改善含硅颗粒在受外部压力时的滑移能力,降低含硅颗粒在与集流体复合过程中的摩擦力和阻力,使含硅颗粒之间从硬接触转变为有滑石粉作为缓冲层的软接触,进一步提高负极活性材料层的致密度,降低负极活性材料层的孔隙率,提高负极的载流子传输能力,增加能量密度,提升负极首圈嵌锂动力学性能,进一步提高电池的首次放电效率。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of silicon anode technology, specifically to an anode sheet and its preparation method, a solid-state battery, and an electrical device. Background Technology
[0002] To improve the energy density of solid-state batteries, high-capacity pure silicon anode materials are often used for the negative electrode. However, pure silicon anode electrodes have low overall compaction density and high porosity. In solid-state batteries, there is no electrolyte in the electrode, and the presence of the porous structure seriously affects the transport of ions and electrons. Summary of the Invention
[0003] The purpose of this disclosure is to provide a negative electrode sheet and its preparation method, a solid-state battery, and an electrical device. The negative electrode sheet has a high compaction density and low porosity of the negative electrode active material layer, which can improve the carrier transport capacity of the negative electrode and improve the first discharge efficiency and lithium intercalation kinetics of the battery.
[0004] To achieve the above objectives, the first aspect of this disclosure provides a negative electrode sheet, the negative electrode sheet comprising a current collector and a negative electrode active material layer disposed on the current collector; the negative electrode active material layer comprises silicon-containing particles and talc powder.
[0005] Optionally, the molecular formula of the talc is Mg3[Si4O] 10 (OH)2; Based on the weight of the silicon-containing particles, the weight percentage of the talc powder is m. 滑 Where, 0.1wt%≤m 滑 ≤8wt%, preferably 2wt%≤m 滑 ≤3wt%.
[0006] Optionally, the talc powder satisfies one or more of the following conditions: The D of the talc 50 Particle size D 50-滑 Where 0.2μm≤D 50-滑 ≤5μm; and / or, The talc powder has a Mohs hardness of M. 滑 Where 0.5≤M 滑 ≤1.5.
[0007] Optionally, the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 , of which 40wt%≤m 硅 ≤97.5wt%, preferably 75wt%~97.5wt%.
[0008] Optionally, the silicon-containing particles satisfy one or more of the following conditions: The silicon-containing particles contain more than 90 wt% silicon. The silicon-containing particles D 50 Particle size D 50-硅 Where 1μm≤D 50-硅 ≤10μm; The Mohs hardness of the silicon-containing particles is M. 硅 Where 6.5≤M 硅 ≤7.5.
[0009] Optionally, the D of the talc powder 50 Particle size and D of the silicon-containing particles 50 The ratio of particle size is d, where 0.1≤d≤3, preferably 0.1≤d≤1.5.
[0010] Optionally, the thickness of one side of the negative electrode active material layer is T, wherein 10μm≤T≤50μm, preferably 10μm≤T≤30μm.
[0011] Optionally, the porosity of the negative electrode active material layer is K, wherein 5% < K < 34%, preferably 7% ≤ K ≤ 20%.
[0012] Optionally, the negative electrode active material layer further includes at least one of a binder, a conductive agent, and sulfide-based solid electrolyte particles, wherein the weight percentage of the binder is m based on the weight of the silicon-containing material. 粘 Where 1wt%≤m 粘 ≤6wt%; and / or, Based on the weight of the silicon-containing material, the weight percentage of the conductive agent is m. 导 Where, 0.5wt%≤m 导 ≤3wt%; and / or, Based on the weight of the silicon-containing material, the weight percentage of the sulfide-based solid electrolyte particles is m. 电解质 Where, 0.1wt%≤m 电解质 ≤100wt%.
[0013] The second aspect of this disclosure provides a method for preparing the negative electrode sheet described in the first aspect of this disclosure, the method comprising: compounding a negative electrode slurry obtained by mixing silicon particles, talc powder and a solvent onto a current collector to obtain a composite material, and drying the composite material to obtain the negative electrode sheet.
[0014] Optionally, the negative electrode active material layer negative electrode slurry further includes at least one of a binder, a conductive agent, and a sulfur-based solid electrolyte.
[0015] Optionally, the solid content of the negative electrode slurry is msolid, wherein 20wt%≤msolid≤65wt%.
[0016] Optionally, the method further includes molding the composite; The forming method includes one or more of roll forming and isostatic pressing. When the forming method includes the rolling process, the conditions for the rolling process include: a pressure of P. 辊 The speed is v, where 5MPa≤P 辊 ≤100MPa, 0.5m / min≤v≤20m / min; and / or, When the molding method includes isostatic pressing, the conditions for isostatic pressing include: a pressure of P. 静 The time is t, where 100MPa≤P 静 ≤600MPa, 5min≤t≤30min.
[0017] A third aspect of this disclosure provides a solid-state battery, including the negative electrode sheet described in the first aspect of this disclosure and / or the negative electrode sheet prepared by the method described in the second aspect of this disclosure.
[0018] This disclosure provides a fourth aspect of a solid-state battery pack, including the solid-state battery described in the third aspect of this disclosure.
[0019] The fifth aspect of this disclosure provides an electrical device comprising a negative electrode sheet as described in the first aspect of this disclosure and / or a negative electrode sheet prepared by the method described in the second aspect of this disclosure and / or a solid-state battery as described in the third aspect of this disclosure and / or a solid-state battery pack provided in the fourth aspect of this disclosure.
[0020] Through the above technical solution, this disclosure adds talc to the negative electrode sheet. The composite layered structure of talc has good lubricity, which can improve the particle rearrangement of silicon particles during the composite process with the current collector, improve the sliding ability of silicon particles under external pressure, reduce the friction and resistance of silicon particles during the composite process with the current collector, and change the hard contact between silicon particles to a soft contact with talc as a buffer layer. This further improves the density of the negative electrode active material layer, reduces the porosity of the negative electrode active material layer, improves the carrier transport capacity of the negative electrode, increases the energy density, improves the first-cycle lithium insertion kinetics performance of the negative electrode, and further improves the first discharge efficiency of the battery.
[0021] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Detailed Implementation
[0022] The following provides a detailed description of specific embodiments of this disclosure. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of this disclosure.
[0023] The first aspect of this disclosure provides a negative electrode sheet, which includes a current collector and a negative electrode active material layer disposed on the current collector; the negative electrode active material layer includes silicon-containing particles and talc powder.
[0024] In this disclosure, due to the good lubricity of the composite layered structure of talc, adding talc to the negative electrode sheet can improve the particle rearrangement of silicon particles during the composite process with the current collector, improve the slippage ability of silicon particles under external pressure, reduce the friction and resistance of silicon particles during the composite process with the current collector, and change the hard contact between silicon particles to a soft contact with talc as a buffer layer. This further improves the density of the negative electrode active material, reduces the porosity of the negative electrode active material, improves the carrier transport capacity of the negative electrode, increases the energy density, enhances the first-cycle lithium insertion kinetics performance of the negative electrode, and further improves the first discharge efficiency of the battery.
[0025] In this disclosure, D 50 Particle size refers to the particle size value corresponding to a cumulative particle size distribution percentage of 50% in a sample.
[0026] According to one embodiment of this disclosure, the molecular formula of talc is Mg3[Si4O] 10 ](OH)2.
[0027] In one embodiment, after disassembling the battery, negative electrode powder can be scraped off from the negative electrode sheet and tested using an X-ray powder diffractometer. When the XRD pattern shows characteristic peaks at 2θ of 9°~10°, 19.3°~20.3°, and 28°~29°, it indicates that talc is present in the negative electrode active material layer. The characteristic peak at 9°~10° corresponds to the (001) crystal plane of talc, the characteristic peak at 19.3°~20.3° corresponds to the (002) crystal plane of talc, and the characteristic peak at 28°~29° corresponds to the (003) crystal plane of talc.
[0028] According to one embodiment of this disclosure, based on the weight of silicon-containing particles, the weight percentage of talc powder is m. 滑 Where 0.1wt%≤m 滑 ≤8wt%, for example, can be any value within the range of 0.1wt%, 0.2wt%, 0.3wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, or any combination thereof, preferably 2wt%≤m 滑≤3wt%. In the above embodiments, the negative electrode active material layer contains an appropriate amount of talc powder, which can effectively improve the particle packing state of silicon particles during the composite process with the current collector, realize the particle rearrangement of silicon particles, and avoid excessive talc powder filling the pores, thus preventing the porosity of the negative electrode active material layer from decreasing and affecting the carrier transport capacity of the negative electrode. Within the above-mentioned preferred talc powder weight percentage range, the soft contact state during the composite process of silicon particles and current collector can be further improved, the compaction density of the negative electrode active material layer can be further increased, and the porosity can be reduced, so that the porosity is within a more optimal range. This is beneficial to improving the carrier transport capacity of the negative electrode, increasing the energy density, improving the first-cycle lithium insertion kinetics performance of the negative electrode, and further improving the first discharge efficiency of the battery.
[0029] According to one embodiment of this disclosure, the D of talc powder 50 Particle size D 50-滑 Where 0.2μm≤D 50-滑 ≤5μm, for example, can be any value within the range of 0.2μm, 0.3μm, 0.4μm, 0.5μm, 1μm, 1.5μm, 1.6μm, 1.7μm, 2μm, 2.1μm, 2.3μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, or any combination thereof. In the above embodiments, the D of talc powder... 50 Within a suitable particle size range, it is beneficial to form a buffer layer between silicon-containing particles that facilitates sliding, thereby improving particle rearrangement and stacking efficiency during current collector composite process. This, in turn, increases the density of the negative electrode active material layer, reduces the porosity of the negative electrode active material layer, improves the carrier transport capacity of the negative electrode, increases energy density, enhances the first-cycle lithium insertion kinetics performance of the negative electrode, and further improves the first discharge efficiency of the battery.
[0030] According to one embodiment of this disclosure, the Mohs hardness of talc powder is M. 滑 Where 0.5≤M 滑≤1.5, for example, can be any value within the range of 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, or any combination thereof. In the above embodiment, the Mohs hardness of talc powder is not higher than that of silicon-containing particles, which is beneficial for transforming the hard contact between silicon-containing particles into a soft contact with talc powder as a buffer layer. At the same time, the composite layered structure of talc powder has good lubricity, which can improve the particle rearrangement of silicon-containing particles during the composite process with the current collector, improve the slippage ability of silicon-containing particles under external pressure, reduce the friction and resistance of silicon-containing particles during the composite process with the current collector, further improve the density of the negative electrode active material layer, reduce the porosity of the negative electrode active material layer, improve the carrier transport capacity of the negative electrode, increase the energy density, improve the first-cycle lithium intercalation kinetics of the negative electrode, and further improve the first discharge efficiency of the battery.
[0031] According to one embodiment of this disclosure, the weight percentage of silicon element in the silicon-containing particles in the negative electrode active material layer is m. 硅 , of which 40wt%≤m 硅 ≤97.5wt%, for example, can be any value within the range of 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 97wt%, 97.5wt%, or any two of these, preferably 75wt%~97.5wt%. The above embodiments are beneficial for improving the energy density and specific capacity of the battery.
[0032] According to one embodiment of this disclosure, the silicon content in the silicon particles is 90 wt% or more. This embodiment is beneficial for improving the energy density and specific capacity of the battery.
[0033] According to one embodiment of this disclosure, D containing silicon particles 50 Particle size D 50-硅 Where 1μm≤D 50 ≤10μm, for example, can be any value within the range of 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, or any combination thereof. The above embodiments are beneficial for achieving a suitable particle size ratio between silicon-containing particles and additives, which helps to improve the density of the negative electrode active material layer, reduce the porosity of the negative electrode active material layer, improve the carrier transport capacity of the negative electrode, increase energy density, enhance the first-cycle lithium insertion kinetics performance of the negative electrode, and further improve the first-cycle discharge efficiency of the battery.
[0034] According to one embodiment of this disclosure, the Mohs hardness of the silicon-containing particles is M. 硅 Where 6.5≤M 硅 ≤7.5, for example, can be any value within the range of 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, or any combination thereof. The above implementation method is beneficial for improving the energy density and specific capacity of the battery.
[0035] According to one embodiment of this disclosure, the D of talc powder 50 Particle size and D of silicon-containing particles 50 The particle size ratio is d, where 0.1 ≤ d ≤ 3. For example, it can be any value within the range of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 1.0, 1.2, 1.5, 1.7, 1.9, 2.0, 2.3, 2.5, 2.7, 3.0, or any combination thereof, preferably 0.1 ≤ d ≤ 1.5. In the above embodiment, by using a reasonable particle size ratio between talc powder and silicon-containing particles, talc powder can more effectively act as a buffer layer between silicon-containing particles during the current collector composite process. This is beneficial for the formation of a compact particle packing morphology during the composite process, thereby increasing the density of the negative electrode active material layer, reducing the porosity of the negative electrode active material layer, improving the carrier transport capacity of the negative electrode, increasing the energy density, enhancing the first-cycle lithium insertion kinetics of the negative electrode, and further improving the first discharge efficiency of the battery.
[0036] According to one embodiment of this disclosure, the single-sided thickness of the negative electrode active material layer is T, wherein 10 μm ≤ T ≤ 50 μm. For example, it can be any value within the range of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or any combination thereof, preferably 10 ≤ T ≤ 30 μm. In the above embodiment, the preferred thickness range of the negative electrode active material layer is more compatible with the size content of silicon particles and talc, their gradation relationship, and the composite process with the current collector. This further improves the compaction density of the negative electrode active material layer, reduces porosity, enhances the carrier transport capacity of the negative electrode, increases energy density, improves the first-cycle lithium insertion kinetics of the negative electrode, and further improves the first-discharge efficiency of the battery.
[0037] According to one embodiment of this disclosure, the porosity of the negative electrode active material layer is K, where 5% < K < 34%, and K can be any value within the range of 5.01%, 5.5%, 6.0%, 6.1%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%, 22.0%, 25.0%, 27.0%, 28.0%, 29.0%, 30.0%, 32.0%, 33.0%, 33.99%, or any two of these. In the above embodiments, the porosity of the negative electrode active material layer is within a suitable low range, which can avoid the influence of the pore structure on the carrier transport, effectively improve the carrier transport capability of the negative electrode, increase the energy density, improve the first-cycle lithium insertion kinetics performance of the negative electrode, and further improve the first discharge efficiency of the battery.
[0038] According to one embodiment of this disclosure, the porosity of the negative electrode active material layer is K, wherein 7% ≤ K ≤ 20%. In the above preferred embodiment, the negative electrode active material layer has a more suitable low porosity and a higher compaction density, which further improves the carrier transport capability of the negative electrode, increases the energy density, and makes the first-cycle lithium insertion kinetics performance and first discharge efficiency of the negative electrode better.
[0039] According to one embodiment of this disclosure, the negative electrode active material layer further includes at least one of a binder, a conductive agent, and sulfur-based solid electrolyte particles.
[0040] According to one embodiment of this disclosure, the negative electrode active material layer further includes a binder, wherein the weight percentage of the binder is m, based on the weight of the silicon-containing particles. 粘 Where 1wt%≤m 粘 ≤6wt%, for example, can be any value within the range of 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, 6.0wt%, or any combination thereof. The above embodiments improve the adhesion between the negative electrode active material layer and the current collector, while also increasing the compaction density of the negative electrode active material layer, reducing porosity, improving the carrier transport capacity of the negative electrode, increasing energy density, enhancing the first-cycle lithium insertion kinetics of the negative electrode, and further improving the first discharge efficiency of the battery.
[0041] According to one embodiment of this disclosure, the adhesive can be of conventional types in the art, and this disclosure does not impose any special limitations on it. For example, it can be one or more of polyacrylic acid (PAA), polythiophene, polypyrrole, polytetrafluoroethylene, nitrile rubber, sodium carboxymethyl cellulose, and polyvinylidene fluoride.
[0042] According to one embodiment of this disclosure, the negative electrode active material layer may include a conductive agent, wherein the weight percentage of the conductive agent is m, based on the weight of the silicon-containing material. 导 Where, 0.5wt%≤m 导 ≤3wt%, for example, can be any value within the range of 0.5wt%, 0.7wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.3wt%, 1.5wt%, 1.7wt%, 2.0wt%, 2.1wt%, 2.3wt%, 2.5wt%, 2.7wt%, 3.0wt%, or any combination thereof. The above implementation method is beneficial for improving the conductivity of the negative electrode, further improving the battery's initial discharge efficiency and lithium intercalation kinetics.
[0043] According to one embodiment of this disclosure, the conductive agent can be of conventional types in the art, such as one or more of carbon black, carbon nanotubes, and carbon nanofibers (VGCF). This embodiment is beneficial for improving the conductivity of the negative electrode, further enhancing the battery's initial discharge efficiency and lithium intercalation kinetics.
[0044] According to one embodiment of this disclosure, the negative electrode active material layer further includes sulfur-based solid electrolyte particles, wherein the weight percentage of the sulfur-based solid electrolyte particles is m, based on the weight of the silicon-containing material. 电解质 Where, 0.1wt%≤m 电解质 ≤100wt%, for example, can be any value within the range of 0.1wt%, 1.0wt%, 10.0wt%, 20.0wt%, 50.0wt%, 80.0wt%, 100.0wt%, or any two of these. The above implementation method is beneficial for improving the carrier transport capability of the negative electrode, further improving the first discharge efficiency of the battery.
[0045] The second aspect of this disclosure provides a method for preparing the negative electrode sheet of the first aspect of this disclosure, the method comprising: compounding a negative electrode slurry obtained by mixing silicon particles, talc powder and solvent onto a current collector to obtain a composite material, and drying the composite material to obtain the negative electrode sheet.
[0046] According to one embodiment of this disclosure, the negative electrode slurry further includes at least one of a binder, a conductive agent, and a sulfur-based solid electrolyte.
[0047] According to one embodiment of this disclosure, the negative electrode active material layer further includes a binder, wherein the weight percentage of the binder is m, based on the weight of the silicon-containing particles. 粘 Where 1wt%≤m 粘 ≤6wt%, for example, can be any value within the range of 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, 5.5wt%, 6.0wt%, or any combination thereof. The above embodiments can improve the adhesion between the negative electrode active material layer and the current collector, while also increasing the compaction density of the negative electrode active material layer, reducing porosity, improving the carrier transport capacity of the negative electrode, increasing energy density, enhancing the first-cycle lithium insertion kinetics of the negative electrode, and further improving the first discharge efficiency of the battery.
[0048] According to one embodiment of this disclosure, the negative electrode active material layer further includes a conductive agent, wherein the weight percentage of the conductive agent is m, based on the weight of the silicon-containing material. 导 Where, 0.5wt%≤m 导 ≤3 wt%, for example, can be any value within the range of 0.5 wt%, 0.7 wt%, 0.9 wt%, 1.0 wt%, 1.1 wt%, 1.3 wt%, 1.5 wt%, 1.7 wt%, 2.0 wt%, 2.1 wt%, 2.3 wt%, 2.5 wt%, 2.7 wt%, 3.0 wt%, or any combination thereof. The above implementation method is beneficial for improving the conductivity of the negative electrode, further improving the battery's initial discharge efficiency and lithium intercalation kinetics.
[0049] According to one embodiment of this disclosure, the negative electrode active material layer further includes sulfur-based solid electrolyte particles, wherein the weight percentage of the sulfur-based solid electrolyte particles is m, based on the weight of the silicon-containing material. 电解质 Where, 0.1wt%≤m 电解质 ≤100wt%, for example, can be any value within the range of 0.1wt%, 1.0wt%, 10.0wt%, 20.0wt%, 50.0wt%, 80.0wt%, 100.0wt%, or any two of these. The above implementation method is beneficial for improving the carrier transport capability of the negative electrode, further improving the first discharge efficiency of the battery.
[0050] According to one embodiment of this disclosure, the solid content of the negative electrode slurry is m. 固 , of which 20wt%≤m 固≤65wt%, for example, can be any value within the range of 20.0wt%, 25.0wt%, 30.0wt%, 35.0wt%, 40wt.0%, 45.0wt%, 50.0wt%, 55.0wt%, 60.0wt%, 65.0wt%, or any two of these.
[0051] According to one embodiment of the present disclosure, the method further includes molding the composite; wherein the molding method includes one or more of roll forming and isostatic pressing.
[0052] In embodiments where the forming method includes roll forming, the roll forming conditions include: a pressure of P. 辊 The speed is v. Where 5MPa≤P 辊 The pressure is ≤100MPa, for example, it can be any value within the range of 5MPa, 10MPa, 20MPa, 50MPa, 60MPa, 70MPa, 80MPa, 90MPa, 100MPa, or any combination thereof; 0.5m / min≤v≤20m / min, for example, it can be any value within the range of 0.5m / min, 1m / min, 1.5m / min, 2m / min, 5m / min, 6m / min, 7m / min, 8m / min, 10m / min, 12m / min, 15m / min, 17m / min, 18m / min, 20m / min, or any combination thereof, preferably 2m / min≤v≤10m / min. The above embodiments are beneficial for preparing a suitable negative electrode, increasing the compaction density of the negative electrode active material layer, reducing porosity, improving the carrier transport capacity of the negative electrode, increasing energy density, improving the first-cycle lithium insertion kinetics of the negative electrode, and further improving the first discharge efficiency of the battery.
[0053] In embodiments where the molding method includes isostatic pressing, the conditions for isostatic pressing include: a pressure of P. 静 The time is t. Where 100MPa≤P 静 ≤600MPa, for example, can be any value within the range of 100MPa, 150MPa, 200MPa, 250MPa, 300MPa, 350MPa, 400MPa, 450MPa, 500MPa, 550MPa, 600MPa, or any combination thereof, preferably 300MPa≤P 静≤500MPa; 5min≤t≤30min, for example, it can be any value within the range of 5min, 10min, 15min, 20min, 25min, 30min, or any combination thereof. The above implementation method is beneficial for preparing a suitable negative electrode, increasing the compaction density of the negative electrode active material layer, reducing porosity, improving the carrier transport capacity of the negative electrode, increasing energy density, enhancing the first-cycle lithium insertion kinetics of the silicon negative electrode, and further improving the first-discharge efficiency of the battery.
[0054] According to one embodiment of the present disclosure, the method includes: premixing silicon-containing particles with talc powder; preparing a negative electrode slurry by mixing the premixed mixture, binder and solvent through aqueous slurry preparation; coating the negative electrode slurry onto a current collector and drying it to obtain a negative electrode active material layer; and composite the negative electrode active material layer with the current collector.
[0055] According to one embodiment of this disclosure, the current collector is a conventional type in the art, and this disclosure does not impose any special limitations on it, such as copper foil; the solvent can be a conventional type in the art, such as one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), anisole (ANI), butyl butyrate (BB), and xylene (XYL).
[0056] A third aspect of this disclosure provides a solid-state battery, including a negative electrode sheet of the first aspect of this disclosure and / or a negative electrode sheet prepared by the method of the second aspect of this disclosure.
[0057] According to one embodiment of the present disclosure, the solid-state battery includes a solid electrolyte layer, which may be a sulfur-based solid electrolyte, including one or more of lithium phosphorus-sulfur-chlorine solid electrolyte (LPSC), lithium germanium phosphorus-sulfur solid electrolyte (LGPS), and lithium phosphorus-sulfur solid electrolyte (LPS).
[0058] It should be noted that the solid-state battery disclosed herein may include, but is not limited to, single cell, battery module, battery pack, etc. That is, the actual application form of the battery provided herein may be, but is not limited to, the listed products, or other application forms. When the battery is a single cell, it includes at least one of cylindrical cells, prismatic cells, etc.
[0059] This disclosure provides a fourth aspect of a solid-state battery pack, including the solid-state battery of the third aspect of this disclosure.
[0060] The fifth aspect of this disclosure provides an electrical device including a negative electrode sheet of the first aspect of this disclosure and / or a negative electrode sheet prepared by the method of the second aspect of this disclosure and / or a solid-state battery of the third aspect of this disclosure and / or a solid-state battery pack provided by the fourth aspect of this disclosure.
[0061] It should be noted that the aforementioned electrical equipment can be any equipment that conventionally requires electricity, such as, but not limited to, computers, vehicles, electric vehicles, air conditioners, refrigerators, washing machines, microwave ovens, printers, fax machines, etc.
[0062] The present disclosure will be further illustrated by the following examples, but the present disclosure is not limited thereto.
[0063] The following embodiments of this disclosure include the following test content: The specific method for testing the weight percentage of talc is as follows: After disassembling the battery, remove the negative electrode plate and the current collector. First, soak the negative electrode active material layer in water, then dissolve the negative electrode active material with hydrofluoric acid (HF). Quantitatively detect the magnesium content in the solution using inductively coupled plasma (ICP-OES / MS), and then calculate the weight percentage of talc using the following formula: The weight percentage of talc powder = (weight content of magnesium / 0.19) × 100%.
[0064] The specific method for testing the Mohs hardness of silicon-containing particles and talc is as follows: The surface of the test material is scratched with a standard mineral of known hardness to determine the test material's ability to resist mechanical scratches. The test material is then observed through a microscope or magnifying glass. If the test material is scratched, its hardness is lower than that of the standard mineral; conversely, if the standard mineral is scratched, the test material is harder. Through step-by-step testing, the highest tolerance level of the test material in the Mohs hardness table is determined, with hardness levels ranging from the softest talc (level 1) to the hardest diamond (level 10).
[0065] D-values of silica-containing particles and talc were tested using a laser particle size analyzer. 50 Particle size; test method refers to GB / T 19077-2016.
[0066] The test method for the porosity of the negative electrode active material layer includes: after disassembling the battery, removing the negative electrode sheet, and testing the porosity of the negative electrode active material layer using the mercury intrusion porosimetry method (GB / T21650.1-2008); The thickness of the negative electrode active material layer was measured using a micrometer.
[0067] Example 1 The silicon-containing particles used in this embodiment (the weight percentage of silicon in the silicon-containing particles is 99 wt%, D) 50 Particle size = 2μm, Mohs hardness M 硅 =7.0), with the addition of talc (commercially available, molecular formula Mg3[Si4O3]2). 10 (OH)2, Mohs hardness M 滑 =1,D 50The particle size is 1.2 μm, and the binder is polyacrylic acid (PAA). Silicon-containing particles and talc powder were premixed in a powder premixer at a mass ratio of 100:2 for 30 minutes. A negative electrode slurry was prepared by aqueous slurry preparation, mixing the mixture with a binder and solvent water. The solid content of the negative electrode slurry was m. 固 The binder has a weight percentage of 4 wt%, based on the weight of the silicon-containing particles (35 wt%). The uniformly mixed negative electrode slurry is coated onto the current collector and dried to obtain a current collector containing a negative electrode active material layer. Based on the weight of the negative electrode active material layer, the weight percentage of silicon-containing particles is 94.3 wt%, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 The content is 93.4 wt%; the single-sided thickness T of the negative electrode active material layer is 20 μm; the negative electrode active material layer and the current collector are subjected to isostatic pressing, and the isostatic pressing pressure P is 93.4 wt%. 静 The negative electrode was obtained by applying a pressure of 500 MPa and a time of t of 10 min.
[0068] A lithium-indium alloy is used as the counter electrode, and LPSC is used as the solid electrolyte layer to form a half cell with the negative electrode.
[0069] Example 2 This embodiment uses the same method as Embodiment 1, except that the mass ratio of silicon-containing particles to talc is 100:0.5, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 It is 94.7 wt%.
[0070] Example 3 This embodiment uses the same method as Embodiment 1, except that the mass ratio of silicon-containing particles to talc is 100:1, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 It is 94.3 wt%.
[0071] Example 4: This embodiment uses the same method as Embodiment 1, except that the mass ratio of silicon-containing particles to talc is 100:3, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 It is 92.5 wt%.
[0072] Example 5 This embodiment uses the same method as Embodiment 1, except that the mass ratio of silicon-containing particles to talc is 100:4, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 It is 91.6 wt%.
[0073] Example 6 This embodiment uses the same method as Embodiment 1, except that the mass ratio of silicon-containing particles to talc is 100:8, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 It is 88.4 wt%.
[0074] Example 7 This embodiment uses the same method as Embodiment 1, the difference being: the D of talc powder 50 The particle size is 0.2 μm.
[0075] Example 8 This embodiment uses the same method as Embodiment 1, the difference being: the D of talc powder 50 The particle size is 1 μm.
[0076] Example 9 This embodiment uses the same method as Embodiment 1, the difference being: the D of talc powder 50 The particle size is 3μm.
[0077] Example 10 This embodiment uses the same method as Embodiment 1, the difference being: the D of talc powder 50 The particle size is 5μm.
[0078] Example 11 This embodiment uses the same method as Embodiment 1, the difference being: the D of talc powder 50 The particle size is 6μm.
[0079] Example 12 This embodiment uses the same method as Embodiment 1, the difference being: the D containing silicon particles 50 The particle size is 0.1 μm.
[0080] Example 13 This embodiment uses the same method as Embodiment 1, the difference being: the D containing silicon particles 50 The particle size is 1 μm.
[0081] Example 14 This embodiment uses the same method as Embodiment 1, the difference being: the D containing silicon particles 50 The particle size is 10 μm.
[0082] Example 15 This embodiment uses the same method as Embodiment 1, the difference being: the D containing silicon particles 50 The particle size is 11 μm.
[0083] Example 16 This embodiment uses the same method as Embodiment 1, except that the weight percentage of silicon in the silicon-containing particles is 95 wt%, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 It is 89.6 wt%.
[0084] Example 17 This embodiment uses the same method as Embodiment 1, except that the weight percentage of silicon in the silicon-containing particles is 90 wt%, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 It is 84.9 wt%.
[0085] Comparative Example 1 The method of Comparative Example 1 is the same as that of Example 1, except that talc is not added to the negative electrode slurry, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 It is 95.2 wt%.
[0086] Comparative Example 2 Comparative Example 2 uses the same method as Example 17, except that talc is not added to the negative electrode slurry, and the weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 It is 86.5 wt%.
[0087] Test case The porosity of the negative electrode active material layer obtained from the above embodiments and comparative examples was tested. At the same time, the obtained negative electrode sheets were assembled into batteries and half-cell performance was tested. The test results are shown in Table 1.
[0088] The testing methods for half-cell performance include: 1) Specific capacity & first-cycle performance test: constant current discharge at 0.1C rate (lithium insertion) to 1mV (vs. Li+ / Li), rest for 10min, constant current charging at 0.1C rate (lithium removal) to 1.5V (vs. Li+ / Li); 2) Rate performance test: after the first cycle of the battery is tested, lithium insertion is performed at 0.1C to 1mV (vs. Li+ / Li), and lithium removal is performed at 1C rate to 1.5V (vs. Li+ / Li).
[0089] After the battery is completed, it is charged and discharged once at a 0.1C rate. The initial efficiency = discharge capacity / charge capacity × 100%. The battery delithigates at a 1C rate and inserts lithium at a 0.1C rate. The lithium insertion kinetics performance is: 1C lithium insertion capacity / 0.1C lithium insertion capacity.
[0090] Table 1
[0091] As shown in Table 1, the porosity of the negative electrode active material layer disclosed in this invention is small, which improves the carrier transport capacity of the negative electrode and enhances the first discharge efficiency and lithium intercalation kinetics of the battery.
[0092] Furthermore, by comparing Examples 1 to 6, it can be seen that the weight content of talc powder in Examples 1 and 4 is within the preferred range of this disclosure. The negative electrode active material layer of this disclosure has a more suitable porosity, and the battery's first discharge efficiency and lithium intercalation kinetics performance are better.
[0093] Furthermore, by comparing Examples 1, 7-15, it can be seen that the D of talc powder in Examples 1, 7-9, and 13-15 is... 50 Particle size and D of silicon-containing particles 50 Within the preferred range of the particle size ratio d in this disclosure, the negative electrode active material layer of this disclosure has a more suitable porosity, resulting in better first discharge efficiency and lithium intercalation kinetics performance of the battery.
[0094] The preferred embodiments of this disclosure have been described in detail above. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.
[0095] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
[0096] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode sheet includes a current collector and a negative electrode active material layer disposed on the current collector; the negative electrode active material layer includes silicon-containing particles and talc powder.
2. The negative electrode sheet according to claim 1, characterized in that, The molecular formula of the talc is Mg3[Si4O] 10 (OH)2; Based on the weight of the silicon-containing particles, the weight percentage of the talc powder is m. 滑 Where, 0.1wt%≤m 滑 ≤8wt%, preferably 2wt%≤m 滑 ≤3wt%.
3. The negative electrode sheet according to claim 1 or 2, characterized in that, The talc powder satisfies one or more of the following conditions: The D of the talc 50 Particle size D 50-滑 Where 0.2μm≤D 50-滑 ≤5μm; and / or, The talc powder has a Mohs hardness of M. 滑 Where 0.5≤M 滑 ≤1.
5.
4. The negative electrode sheet according to claim 1, characterized in that, The weight percentage of silicon in the silicon-containing particles in the negative electrode active material layer is m. 硅 , of which 40wt%≤m 硅 ≤97.5wt%, preferably 75wt%~97.5wt%.
5. The negative electrode sheet according to claim 1 or 4, characterized in that, The silicon-containing particles satisfy one or more of the following conditions: The silicon-containing particles contain more than 90 wt% silicon. The silicon-containing particles D 50 Particle size D 50-硅 Where 1μm≤D 50-硅 ≤10μm; The Mohs hardness of the silicon-containing particles is M. 硅 Where 6.5≤M 硅 ≤7.
5.
6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that, The D of the talc 50 Particle size and D of the silicon-containing particles 50 The ratio of particle size is d, where 0.1≤d≤3, preferably 0.1≤d≤1.
5.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that, The thickness of one side of the negative electrode active material layer is T, wherein 10μm≤T≤50μm, preferably 10μm≤T≤30μm.
8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that, The porosity of the negative electrode active material layer is K, wherein 5% < K < 34%, preferably 7% ≤ K ≤ 20%.
9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that, The negative electrode active material layer further includes at least one of a binder, a conductive agent, and sulfide-based solid electrolyte particles, wherein the weight percentage of the binder is m based on the weight of the silicon-containing material. 粘 Where 1wt%≤m 粘 ≤6wt%; and / or, Based on the weight of the silicon-containing material, the weight percentage of the conductive agent is m. 导 Where, 0.5wt%≤m 导 ≤3wt%; and / or, Based on the weight of the silicon-containing material, the weight percentage of the sulfide-based solid electrolyte particles is m. 电解质 Where, 0.1wt%≤m 电解质 ≤100wt%.
10. A method for preparing the negative electrode sheet according to any one of claims 1 to 9, characterized in that, The method includes: mixing silicon-containing particles, talc powder and solvent to obtain a negative electrode slurry, which is then compounded onto a current collector to obtain a composite material, and drying the composite material to obtain the negative electrode sheet.
11. The method according to claim 10, characterized in that, The negative electrode slurry also includes at least one of a binder, a conductive agent, and a sulfur-based solid electrolyte.
12. The method according to claim 10, characterized in that, The solid content of the negative electrode slurry is m 固 , of which 20wt%≤m 固 ≤65wt%.
13. The method according to any one of claims 10 to 12, characterized in that, The method further includes molding the composite; The forming method includes one or more of roll forming and isostatic pressing. When the forming method includes the rolling process, the conditions for the rolling process include: a pressure of P. 辊 The walking speed is v, where 5MPa≤P 辊 ≤100MPa, 0.5m / min≤v≤20m / min; and / or, When the molding method includes isostatic pressing, the conditions for isostatic pressing include: a pressure of P. 静 The time is t, where 100MPa≤P 静 ≤600MPa, 5min≤t≤30min.
14. A solid-state battery, characterized in that, Includes the negative electrode sheet according to any one of claims 1 to 9 and / or the negative electrode sheet prepared by the method according to any one of claims 10 to 13.
15. A battery pack, characterized in that, Includes the solid-state battery as described in claim 14.
16. An electrical appliance, characterized in that, It includes one or more of the following: the negative electrode sheet according to any one of claims 1 to 9, the negative electrode sheet prepared by the method according to any one of claims 10 to 13, the solid-state battery according to claim 14, and the battery pack according to claim 15.